DNA damage response and repair gene mutations are associated with tumor mutational burden and outcomes to platinum-based chemotherapy/immunotherapy in advanced NSCLC patients - Weiguang Gu; Wenya Zhuang; Mengxia Zhuang; Minhong He; Zhihua Li (Diagnostic Pathology, 2023)
Abstract Background DNA damage response and repair (DDR) genes are crucial for maintaining the integrity of the genome. This study aims to explore the correlation of DDR gene mutations with TMB, clinical characteristics, and outcomes to platinum-based chemotherapy and platinum-based chemotherapy/immunotherapy in non-small cell lung cancer (NSCLC) without EGFR and ALK alterations. Methods Tumor tissue from 49 patients with stage III or IV NSCLC who were without EGFR and ALK alterations were analyzed using targeted next-generation sequencing (NGS). Among them, 13 patients received first-line platinum-based chemotherapy, 32 patients received first-line platinum-based chemotherapy/immunotherapy. Results In these NSCLC patients without EGFR and ALK alterations, the frequently mutated genes included TP53, KMT2D and KRAS, the most frequently mutated DDR gene was FANCG, DDR gene mutations were detected in 20 patients. The mutation frequency of homologous recombination (HR) pathway was significantly higher in lung squamous cell carcinoma (LUSC) than that in lung adenocarcinoma (LUAD) (30.8% vs. 5.7%). Among DDR positive patients, a lower percentage exhibited metastasis. Patients with DDR gene mutations, cell-cycle checkpoint pathway mutations, and BER pathway mutations had significantly higher TMB compared to those without corresponding mutations. In the patients receiving platinum-based chemotherapy/immunotherapy, the disease control rate was significantly lower in the DDR-positive group compared with that in the DDR-negative group (55.6% vs. 100.0%). Among LUAD patients receiving platinum-based chemotherapy/immunotherapy, we observed a worse overall survival (OS) in DDR-positive group, as well as poorer progression-free survival(PFS)and OS in BER-positive and FANCG mutated group. Conclusions DDR gene mutations are associated with tumor metastasis, TMB, and outcomes to platinum-based chemotherapy/immunotherapy in advanced NSCLC patients.